Bulgaria : Mitigating the Impact of the Economic Crisis on the Poor, Social Safety Net Reform Policy Note - World Bank (Washington, DC, 2013)
This report aims to inform the discussion by summarizing recent World Bank analysis on the performance of the social safety net on the basis of the 2007 Multi-Topic Household Survey. It reviews the effectiveness of the main social safety net transfer programs in reducing poverty and assesses how well they are placed both to address the possible social impact of the crisis and to promote active social inclusion. It also reviews the effectiveness of recently introduced limits to eligibility to Guaranteed Minimum Income, the main social assistance benefit, which aimed at raising work incentives for beneficiaries. It finally lays out a set of policy recommendations on how to strengthen the social safety net to deal with the economic crisis in the short term as well as to promote employment activation and support broader a human development agenda over the medium term.